2015
DOI: 10.1007/s00191-015-0432-6
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous economic order

Abstract: This paper provides an attempt to formalize Hayek's notion of spontaneous order within the framework of the Arrow-Debreu economy. Our study shows that if a competitive economy is enough fair and free, then a spontaneous economic order shall emerge in long-run competitive equilibria so that social members together occupy an optimal distribution of income. Despite this, the spontaneous order might degenerate in the form of economic crises whenever an equilibrium economy approaches the extreme competition. Remark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
72
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(80 citation statements)
references
References 35 publications
(47 reference statements)
0
72
0
1
Order By: Relevance
“…However, Tao has considered the case of multiple industries. 17 Given the above economy, if each consumer's preferences are strictly convex and if each¯rm's production possibility sets are strongly convex, there exists a unique general equilibrium allocation ðx (i) Every consumer's utility is maximal; (ii) Every¯rm's pro¯t is maximal; (iii) Market clearing:…”
Section: Microstates and General Equilibriamentioning
confidence: 99%
See 4 more Smart Citations
“…However, Tao has considered the case of multiple industries. 17 Given the above economy, if each consumer's preferences are strictly convex and if each¯rm's production possibility sets are strongly convex, there exists a unique general equilibrium allocation ðx (i) Every consumer's utility is maximal; (ii) Every¯rm's pro¯t is maximal; (iii) Market clearing:…”
Section: Microstates and General Equilibriamentioning
confidence: 99%
“…11 Following Marshall's tradition, long-run competition is identi¯ed with a belief that every¯rm can freely enter and exit any industry. 19 Tao 17 showed that such a belief leads to two constraints for the production sets:…”
Section: Microstates and General Equilibriamentioning
confidence: 99%
See 3 more Smart Citations